PENGARUH MASA KERJA DAN TINGKAT PENDIDIKAN TERHADAP KOMPETENSI KARYAWAN DENGAN COMPETENCY BASED TRAINING SEBAGAI VARIABEL INTERVENING (STUDI PADA KARYAWAN UNIT SPINNING PT APAC INTI CORPORA) - Putra, Yanuar Surya; Pujiasih, Sri; Mar'ati, Fudji Sri (AMONG MAKARTI, 2010)
The purpose of this research is to know the influence of working periode and education level toward worker competency with competency based training as intervening variable in PT. Apac Inti Corpora., with parsially test, simultaneous test from dependent variable, intervening and dependent variable. There is explain that independent variabel is working period and education level, intervening variabel is competency based training. The sample of the research is 32 worker of spinning unit in PT. Apac Inti Corpora. Data for the research is use secondary. To answers the research question is analyze using path analysis. Kata kunci : Masa kerja, tingkat pendidikan, Competency based training, Kompetensi karyawan.